Effect of the inclusion of fractions of Saccharomyces cerevisiae culture on the in vitro ruminal fermentation of star grass (Cynodon nlemfuensis) - Marrero, Yoandra; Mart?n, Elizabeth; Rodr?guez, D.; Galindo, Juana (Cuban Journal of Agricultural Science, 2010)
The in vitro gas production technique was used to determine the effect of Saccharomyces cerevisiae on the nutritive value of DM and NDF of star grass (Cynodon nlemfuensis). Three forms of yeast inclusion were evaluated: 1) culture medium inoculated with S. cerevisiae, 2) granulate from the centrifugation of the inoculated culture medium, 3) supernatant from the centrifugation of the inoculated culture medium. Also, a control was included without yeast. An analysis of variance was performed, according to completely randomized design with four treatments for the indicator gas production and according to random block design for the measures of pH, DM and NDF degradability and count of ruminal microbial populations (total and cellulolytic bacteria, cellulolytic fungi). The gas production was measured every 10 min and the rest of the indicators at 24 h. Four replicates were conducted. There were increases in the number of cellulolytic and total bacteria after the inclusion of S. cerevisiae in the culture medium (7.87x108 and 19.7x108 cfu.mL-1, respectively), generating a positive response in the in vitro degradation rate, and, consequently, in the accumulated gas production. Nevertheless, the inclusion of granulate of yeast showed a positive effect when using the fraction dry matter, but not in NDF. The supernatant of the yeast culture caused deleterious effects on all the response variables. The results permitted to state that, when including S. cerevisiae both at the culture medium and in the form of granulate, the in vitro fermentative processes were favored exerting populations of total viable and cellulolytic bacteria in the DM and NDF of C. nlemfuensis, which was reflected in the degradability increase. Key words: rumen, microorganisms, gas production, yeast.